Hubungan Indeks Massa Tubuh (IMT), Asupan Purin DanOlahraga Dengan Kejadian Gout Arthritis Pada Lansia Di Wilayah Kerja Puskesmas Tanjungsari Pacitan - Fauzan, Aldhi, Yuli Kusumawati, SKM, M.Kes (2017)
Gout arthritis is a disease caused due to accumulation of monosodium urate crystals in the body. Prevalence of gout arthritis that occur in the elderly in East Java 26.4% and in Pacitan 13.2%. The purpose of this study was to investigate the relationship between body mass index (BMI), purine intake, and exercise with the incidence of gout arthritis in the elderly in Puskesmas Tanjungsari Pacitan. This research method using observational design with case control approach. The study population was elderly as many as 152 people each 76 for cases and controls. Selection of the sample in the case of using a simple random sampling and the control is taken of the elderly nearest neighbors of the case. The statistical test used chi square. The results showed that there is a correlation between BMI with the incidence of gout arthritis (p<0.001), there is a correlation between the intake of purine with the incidence of gout arthritis (p<0.001), and a correlation with the incidence of gout arthritis exercise (p<0,001) in Puskesmas Tanjungsari Pacitan.